Orígenes: desdibujando frontera (2020)
Origins is a project in which, through the evocation of the history of my parents, I seek to explore memories and emotions that allow me to explore my origins and discover my identity. It is a work of family introspection to understand my cultural syncretism, which has been strongly present throughout my life. This project, then, aims to create a unique piece of design that becomes an object of remembrance and tradition. From the feelings that the kimono transmits to me, it is intended to intervene this garment as a canvas that allows me to remember my Japanese family heritage and merge it, through ornamentation and the craft of weaving, with the colorful, passionate, and creative that I have inherited from my mother and my maternal family, that extroverted part that has always been present in us and is characterized by its spontaneity, emotionality, creativity and love. Finally, I hope that this garment can be transformed, in the future, into the gift that I once received from my Japanese grandmother but that this time it symbolizes a different origin, mine. This is an artistic expression that allows me to understand where I come from. It is also a tribute to the love of my parents who allowed me to exist, and given the improbability of my genes, considering that Japan is one of the countries with the least migration in the world and there is a great distance between both countries, it is extraordinary to know where I am from and have this cultural crossroads so atypical, but so incredible that I have.